Opioid Prescribing Patterns and Usage Following Cochlear Implantation. Issue 7 (August 2020) - Mahairas, Anthony D.; Neff, Ryan; Craker, Nikki; McNulty, Beth N.; Shinn, Jennifer B.; Bush, Matthew L.
Abstract : Objective: To evaluate opioid prescribing patterns following cochlear implantation (CI) and assess factors associated with recurrent opioid use. Study Design: Retrospective cohort study. Setting: National pharmaceutical database recording opioid fulfillment (Truven Health Marketscan Commercial Claims and Encounters and Medicare Claims and Encounters database) Participants: CI recipients who filled opioid prescriptions between January 2011 and December 2016. All patients had no previous opioid prescriptions filled 60 days before implantation and filled at least one opioid prescription within 1 week after surgery. Cohort 1 filled only one prescription and cohort 2 filled more than one prescription in the 12 months following CI. Univariate/multivariate analysis was performed to assess for associations with recurrent opioid use. Main Outcome Measure(s): Opioid prescription details and recurrent opioid use. Results: The study included 98 patients (cohort 1 = 57, cohort 2 (recurrent opioid use) = 41). Hydrocodone 5 mg was most frequently used. The average duration opioids were prescribed was 5.49 days with an average quantity of tablets of 36.1. Recurrent opioid use in cohort 2 was associated with both total morphine milligram equivalents (MME) prescribed/day in the first postoperative week (OR = 1.03, p  = 0.01) and use of stronger MME opioids (OR = 7.20, p  = 0.05). Conclusion: Prescribing patterns following CI can influence recurrent opioid use in patients. Each additional tablet of hydrocodone 5 mg beyond 8 tablets/d or oxycodone 5 mg beyond 5.33 tablets/d, increases the likelihood of recurrent opioid use by 15 or 22.5%, respectively. Limiting opioids prescribed per day to no more than 40 MME could lower the likelihood of patients becoming recurrent opioid users postoperatively.